Getting beyond better - Martin, Roger L. (Harvard Business Review Press, 2015)
The book begins with a probing and useful theory of social entrepreneurship, moving through history to illuminate what it is, how it works, and the nature of its role in modern society. The authors then set out a framework for understanding how successful social entrepreneuars actually go about producing transformative change. There are four key stages: understanding the world; envisioning a new future; building a model for change; and scaling the solution. With both depth and nuance, Martin and Osberg offer rich examples and personal stories and share lessons and tools invaluable to anyone who aspires to drive positive change, whatever the context